2014
DOI: 10.3109/10717544.2014.960981
|View full text |Cite
|
Sign up to set email alerts
|

Effective topical delivery systems for corticosteroids: dermatological and histological evaluations

Abstract: Atopic dermatitis (AD) is a chronic and relapsing skin disease with severe eczematous lesions. Long-term topical corticosteroid treatment can induce skin atrophy, hypopigmentation and transepidermal water loss (TEWL) increase. A new treatment approach was needed to reduce the risk by dermal targeting. For this purpose, Betamethasone valerate (BMV)/Diflucortolone valerate (DFV)-loaded liposomes (220-350 nm) were prepared and incorporated into chitosan gel to obtain adequate viscosity ($13 000 cps). Drugs were l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…Liposomes are microscopic structures consisting of one or more concentric spheres of lipid bilayers enclosing aqueous compartments. Liposomes have been successfully used to encapsulate lipophilic and hydrophilic compounds (Eroglu et al, 2014;Johal et al, 2014;Ali et al, 2014;El-badry et al, 2014;Fang et al, 2015). In the dermatological field, liposomes were used initially only because of their moisturizing and restoring action.…”
Section: Introductionmentioning
confidence: 99%
“…Liposomes are microscopic structures consisting of one or more concentric spheres of lipid bilayers enclosing aqueous compartments. Liposomes have been successfully used to encapsulate lipophilic and hydrophilic compounds (Eroglu et al, 2014;Johal et al, 2014;Ali et al, 2014;El-badry et al, 2014;Fang et al, 2015). In the dermatological field, liposomes were used initially only because of their moisturizing and restoring action.…”
Section: Introductionmentioning
confidence: 99%
“…In the nanocarrier literature reviewed here, only two-thirds of the articles mentioned nanocarrier toxicity. Most articles referred to previous work using in vitro models, while some performed their own toxicity screening in vitro using either human fibroblasts or keratinocytes, and examining cell death as the only metric [ 103 , 107 , 110 , 118 , 123 , 124 , 127 ]. Some researchers also examined gross toxicity and potential irritant effects [ 95 , 96 , 112 ], and Pople et al performed the most comprehensive toxicity assessment with a 28-day toxicity study that examined multiple target organs for histological abnormalities [ 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fontana et al used 200-nm lipid core nanocapsules to deliver clobetasol propionate, and they found that when treating Wistar rats with nickel sulfate-induced dermatitis, there was a slower drug release compared to drugs without the nanocarrier [ 102 ]. More recently, Eroglu et al used liposomes measuring 220–350 nm to apply betamethasone valerate and diflucortolone valerate to DNFB-induced atopic dermatitis skin in Wistar rats [ 103 ]. They observed similar therapeutic effects when compared to currently available corticosteroid creams that contain 10 times the dose applied in the nanocarriers.…”
Section: Transdermal Nanocarriers For the Treatment Of Skin Diseasmentioning
confidence: 99%
“…The liposomes showed 2.68-and 3.22-fold higher retention, respectively for BMV and DFV in stratum corneum and epidermis when compared with available commercial cream. Cell culture studies, trans-epidermal water loss (TEWL) measurements and histological observations confirmed that liposome in gel formulation was safe to be used in treating AD [72].…”
Section: Liposomesmentioning
confidence: 79%